2018
DOI: 10.1186/s13012-018-0796-8
|View full text |Cite
|
Sign up to set email alerts
|

How do physicians behave when they participate in audit and feedback activities in a group with their peers?

Abstract: BackgroundAudit and feedback interventions may be strengthened using social interaction. With this in mind, the Calgary office of the Alberta Physician Learning Program developed a process for audit and group feedback for physician groups. As a part of a larger project to develop a practical approach to the design and implementation of audit and group feedback projects, we explored patterns of physician behavior during facilitated audit and group feedback sessions.MethodsSix audit and group feedback sessions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(93 citation statements)
references
References 27 publications
4
82
0
2
Order By: Relevance
“…Here, we extend our previous work, which examined physician responses to a novel type of audit and group feedback (AGF) and presented a conceptual model of physician responses to AGF sessions (AGFS) [ 8 ]. We observed that physicians engaged in planning for change more robustly in some AGFS than in others.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Here, we extend our previous work, which examined physician responses to a novel type of audit and group feedback (AGF) and presented a conceptual model of physician responses to AGF sessions (AGFS) [ 8 ]. We observed that physicians engaged in planning for change more robustly in some AGFS than in others.…”
Section: Introductionmentioning
confidence: 89%
“…In a previous study, we described our approach to AF: audit and group feedback sessions (AGFS) [ 8 ]. These AGFS were designed based upon the principles of social learning theory and best practices from the education feedback and implementation science literature [ 7 , 17 , 23 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…We allocated the hospitals into monthly feedback group (A hospital) and quarterly feedback group (B and C hospital), based on the requirement of those hospitals. The reason for allocation was that the compliance of measures uctuated unsteadily in one month in B and C hospital due to less MDROs infected patients and limited observed opportunities, which reduced the conviction of feedback for clinical staff [23].…”
Section: Study Settingmentioning
confidence: 99%
“…The studies included within our review pertain to a broad range of subjects, methods, and outcomes; our summary of the results is not meant for educators to draw any significant conclusions about the efficacy of coaching methods. Finally, due to the lack of clarity in terminology around coaching and mentorship, certain papers, which may have used coaching‐ or mentorship‐like strategies (e.g., group peer review and discussion of practice patterns during audit and feedback), may have been missed in our present search strategy.…”
Section: Limitationsmentioning
confidence: 99%